Parchment Skins and Human Skins: Some Thoughts on the Permeability of Text and Material Environment in Late Antique Jewish Reading Cultures - Wollenberg, Rebecca Scharbach (Hebrew studies, 2023)
Late antique rabbinic Judaism famously left no manuscript traces. Without material evidence regarding early rabbinic practices of reading and writing, scholars have struggled to close the theoretical gap between the physical remnants of epigraphic and ritual writing from Jewish communities in this period and the portraits of reading and writing preserved in medieval manuscripts of late antique rabbinic literature. Yet, Karen Stern has observed that virtually all of the methods adopted to date ultimately privilege rabbinic writings by treating them as the hermeneutical frame through which the material evidence is interpreted. This article asks if we can reverse that hermeneutic hierarchy by (re)reading the literary tradition in light of the insights brought to us by the traces of material writing from the period. As a case study, this article takes the material evidence that visitors to the Dura Europos synagogue engaged with the prepared pictorial texts and architectural spaces of the synagogue in deeply interactive ways - rubbing and touching images and even emending and adding their own words and images to those in the prepared environment. When we reconsider early rabbinic traditions in light of this popular interactive disposition towards text and image, it emerges that many early rabbinic thinkers likewise approached written and pictorial texts as inherently contingent products that invited the continued intervention of other human hands. Moreover, one discovers that many rabbinic texts theorized this interactive relationship as a manifestation of a fundamental continuity and permeability between text and the material world.